Upaya Pencegahan Hand, Foot, and Mouth Disease Berat Melalui Vaksinasi Enterovirus 71: Analisis - Aditya, Thomas (Cermin Dunia Kedokteran, 2024)
Indonesian Ministry of Health detected an increasing trend in suspected hand, foot, and mouth disease (HFMD) in all provinces in Indonesia in 2024. Enterovirus 71 (EV71) is the main cause of severe HFMD and death. There has been no specific therapy for EV71. EV71 vaccine has been developed and approved by regulatory agencies in various countries (China, Thailand, and Indonesia) for the prevention of HFMD due to EV71. Multi-center phase IV study showed a good safety profile with an AEFI of 1,079%. Most AEFIs are grades 1 and 2.